Efficacy and safety of intravenous tranexamic acid administration in patients undergoing hip fracture surgery for hemostasis: A meta-analysis. Issue 21 (May 2017) - Zhang, Pei; He, Jinshan; Fang, Yongchao; Chen, Pengtao; Liang, Yuan; Wang, Jingcheng
Abstract: Background: Patients undergoing hip fracture surgery frequently require blood transfusion. Tranexamic acid (TXA) has been widely used to decrease blood loss and transfusion rates in joint replacement surgery. Therefore, we conducted a meta-analysis to evaluate efficacy and safety of intravenous TXA administration in patients suffering from hip fractures. Methods: Electronic databases were searched before December 2016 by 2 independent reviewers, including Cochrane Library, EMBASE, PubMed, Web of Science, the Chinese Biomedical Literature database, and the China National Knowledge Infrastructure databases. Randomized controlled trials (RCTs) involving the efficacy and safety of intravenous (IV) TXA in patients who underwent hip surgery were included in our meta-analysis. The endpoints included total blood loss, hidden blood loss, postoperative hemoglobin decline, transfusion rates, the rate of thrombotic events, and operative time. Current meta-analysis was performed following the guidelines of the Cochrane Reviewer's Handbook and the PRISMA statement. The pooling of data was carried out using STATA V.12.0 software. Result: Eight RCTs were included, involving 598 participants. Current meta-analysis indicated that the IV TXA group had less total blood loss (weighted mean difference [WMD] = −277, 95%CI: −335 to −220, P = .000), less hidden blood loss (WMD = −246, 95%CI: −252 to −241, P = .000), lower postoperative hemoglobin decline (WMD = −1.36, 95% CI: −1.84 to −0.88, P = .000), and lower transfusion rates (risk difference [RD] = −0.19, 95% CI: −0.27 to −0.11, P = .000) compared to the control group. No significant differences were found regarding the rate of thrombotic events (RD = 0.02, 95% CI: = −0.01 to 0.05, P = .262) and operative time (WMD = −0.7, 95% CI: −3.3 to 1.9, P = .6). Conclusion: It was well established that systemic administration of TXA could reduce blood loss and transfusion rates in hip fracture surgery. But the optimal regimen, dosage, and timing still need a further research. In addition, more large and high-quality randomized controlled studies are needed to focus on the safety of IV TXA application before its wide recommendation for use in hip fracture surgery.